Vibro-impact dynamics - Luo, Albert C. J.; Guo, Yu, 1984- (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
Presents a systematic view of vibro-impact dynamics based on the nonlinear dynamics analysis Comprehensive understanding of any vibro-impact system is critically impeded by the lack of analytical tools viable for properly characterizing grazing bifurcation. The authors establish vibro-impact dynamics as a subset of the theory of discontinuous systems, thus enabling all vibro-impact systems to be explored and characterized for applications. Vibro-impact Dynamics presents an original theoretical way of analyzing the behavior of vibro-impact dynamics that can be exte.
7.4.3 Periodic Motions and Local Stability7.5 Predictions and Simulations; 7.5.1 Bifurcation Scenario; 7.5.2 Analytical Prediction; 7.5.3 Numerical Simulations; Appendix 7.A; References; Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Vibration; Impact; Shock (Mechanics); Impact; Shock (Mechanics); Vibration; SCIENCE -- Nanoscience; Impact; Shock (Mechanics); Vibration; Electronic books; Electronic books